Management of IFES in Brazil in the Thesis and Dissertations of Capes - Moura, Mara Aguida Porfírio; Passos, Guiomar de Oliveira (European Scientific Journal, ESJ, 2017)
The results of the survey carried out in Banco de Teses e Dissertações da Coordenação da CAPES (Thesis and Dissertation Bank of CAPES Coordination) on the management of Brazilian universities after the Reuni are presented, with the objective of verifying an approach to the subject and its results. To do so, 59 papers were selected, only 22 (3 theses and 19 dissertations) deal with a study on the results of the Reuni Program. It is verified that management is dealt with in just 2 works, and the others are related to planning and implementation of Reuni in a particular institution, teaching, program financing, and expansion of under graduation, organizational socialization, access, efficiency assessment, curricular restructuring and student assistance. It is concluded that management is a secondary topic on thesis and dissertations and that the approaches turn to the effects of the foreseen model, sometimes trying to reach the goal of the Program to expand opportunities to access, sometimes administration of Academic units.